2017
DOI: 10.1016/j.spen.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Promise, Progress, and Pitfalls in the Search for Central Nervous System Biomarkers in Neuroimmunological Diseases: A Role for Cerebrospinal Fluid Immunophenotyping

Abstract: Biomarkers are central to the translational medicine strategic focus, though strict criteria need to be applied to their designation and utility. They are one of the most promising areas of medical research, but the “biomarker life-cycle” must be understood to avoid false-positive and false-negative results. Molecular biomarkers will revolutionize the treatment of neurological diseases, but the rate of progress depends on a bold, visionary stance by neurologists, as well as scientists, biotech and pharmaceutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…C–C ligands ( 1 28 ), the largest group of CKs, correspond to C–C receptors (CCRs), just as C–X–C CKs ( 1 17 ), the second largest CK subgroup, do to C–X–C receptors (CXCRs), and there is functional relatedness between subgroup ligands ( 7 ). XCL (two types) and CX3C (one type) are smaller ligand subgroups.…”
Section: Cks/cytokines and Their Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…C–C ligands ( 1 28 ), the largest group of CKs, correspond to C–C receptors (CCRs), just as C–X–C CKs ( 1 17 ), the second largest CK subgroup, do to C–X–C receptors (CXCRs), and there is functional relatedness between subgroup ligands ( 7 ). XCL (two types) and CX3C (one type) are smaller ligand subgroups.…”
Section: Cks/cytokines and Their Receptorsmentioning
confidence: 99%
“…Other small studies also have been reported, but with pitfalls in interpretation ( 1 ). In a study of Aicardi–Goutières syndrome (AGS), multiple CSF cytokine and CK abnormalities were shown ( 125 ), but would not have been significant if correction for multiple comparisons had been made.…”
Section: Comparison Of Csf Ck/cytokine Immunomarker Profiles In Humanmentioning
confidence: 99%
See 2 more Smart Citations
“…43 The EDSS only registers overt deficits and misses the subtle clinical deteriorations in the course of the disease as it is inherently limited by the sensitivity of the clinical examinations that constitute this scale. 44 Finally, the EDSS records clinical information retrospectively, but yields no information on disease progression. 43,45…”
Section: The Status Quo and Limitations Of Current Trial Designsmentioning
confidence: 99%